Development of an Immunochromatographic Test Strip for Detection of Cholera Toxin. (7th November 2013) - Yamasaki, Eiki; Sakamoto, Ryuta; Matsumoto, Takashi; Morimatsu, Fumiki; Kurazono, Takayuki; Hiroi, Toyoko; Nair, G. Balakrish; Kurazono, Hisao
Abstract : Because cholera toxin (CT) is responsible for most of the symptoms induced by Vibrio cholerae infection, detection of CT is critical for diagnosis of the disease. In this study, we constructed an immunochromatographic test strip for detection of CT (CT-IC) with polyclonal antibodies developed against purified recombinant whole CT protein. The detection limit of the CT-IC was 10 ng/mL of purified recombinant CT, and it could detect the CT in culture supernatant of all 15 toxigenic V. cholerae isolates examined, whereas no false-positive signal was detected in all 5 nontoxigenic V. cholerae isolates examined. The specificity of the CT-IC was examined with recombinant heat-labile toxin (LT), which shares high homology with CT, and it was revealed that the minimum detection limit for LT was 100 times higher than that for CT. In addition, lt gene-positive enterotoxigenic Escherichia coli (ETEC) was examined by CT-IC. The false-positive signals were observed in 3 out of 12 ETEC isolates, but these signals were considerably faint. The CT-IC did not develop false-positive signals with all 7 V. parahaemolyticus isolates. These results showed the high specificity of CT-IC and the feasible use of it for the detection and surveillance of toxigenic V. cholerae .